Class Frizzled GPCRs in GtoPdb v.2025.3 (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
Receptors of the Class Frizzled (FZD, nomenclature as agreed by the NC-IUPHAR subcommittee on the Class Frizzled GPCRs [184]), are GPCRs highly conserved across species and were originally identified in Drosophila [21]. While SMO shows structural resemblance to the 10 FZDs, it is functionally separated as it is involved in Hedgehog signaling [184]. SMO exerts its effects by activating heterotrimeric G proteins or stabilization of GLI by sequestering catalytic PKA subunits [191, 6, 62]. While SMO itself is bound by sterols and oxysterols [28, 96], FZDs are activated by WNTs, which are cysteine-rich lipoglycoproteins with fundamental functions in ontogeny and tissue homeostasis. FZD signaling was initially divided into two pathways, being either dependent on the accumulation of the transcription regulator β-catenin or being β-catenin-independent (often referred to as canonical vs. non-canonical WNT/FZD signaling, respectively). Nevertheless, it makes pharmacologically more sense to define downstream signaling by transducer coupling to either DVL or heterotrimeric G proteins [185]. WNT stimulation of FZDs can, in cooperation with the low density lipoprotein receptors LRP5 (O75197) and LRP6 (O75581), lead to the inhibition of a constitutively active destruction complex, which results in the accumulation of β-catenin and subsequently its translocation to the nucleus. β-catenin, in turn, modifies gene transcription by interacting with TCF/LEF transcription factors. WNT/β-catenin-dependent signalling can also be activated by FZD subtype-specific WNT surrogates [142]. β-catenin-independent FZD signalling is far more complex with regard to the diversity of the activated pathways. WNT/FZD signalling can lead to the activation of heterotrimeric G proteins [35, 188, 159], the elevation of intracellular calcium [194], activation of cGMP-specific PDE6 [2] and elevation of cAMP as well as RAC-1, JNK, Rho and Rho kinase signalling [61]. Novel resonance energy transfer-based tools have allowed the study of the GPCR-like nature of FZDs in greater detail. Upon ligand stimulation, FZDs undergo conformational changes and signal via heterotrimeric G proteins [248, 249, 110, 183, 108, 56, 13]. Furthermore, the phosphoprotein Dishevelled constitutes a key transducer in WNT/FZD signaling towards planar-cell-polarity-like pathways. Importantly, FZDs adopt distinct conformational landscapes that regulate pathway selection [249, 54]. As with other GPCRs, members of the Frizzled family are functionally dependent on the arrestin scaffolding protein for internalization [24], as well as for β-catenin-dependent [15] and -independent [93, 16] signalling. The pattern of cell signalling is complicated by the presence of additional ligands, which can enhance or inhibit FZD signalling (secreted Frizzled-related proteins (sFRP), Wnt-inhibitory factor (WIF), sclerostin or Dickkopf (DKK)), as well as modulatory (co)-receptors with Ryk, ROR1, ROR2 and PTK7, which may also function as independent signaling proteins. An important FZD4-selective non-WNT agonist is the norrin cysteine knot protein, which is a key player in FZD4-mediated vascularization for example in the retina and which is functionally related to familial exudative vitreoretinopathy (FEVR).